Molecular study on selected vector-borne infections in urban stray colony cats in northern Italy. Issue 8 (August 2014) - Spada, Eva; Proverbio, Daniela; Galluzzo, Paola; Della Pepa, Alessandra; Perego, Roberta; Bagnagatti De Giorgi, Giada; Ferro, Elisabetta
Feline vector-borne diseases can be caused by a range of pathogens transmitted by arthropods. Many of these infections have zoonotic implications, and stray cats are potential sentinels for human and pet health. This study investigated the prevalence of selected vector-borne infections in stray colony cats in Milan. Blood samples from 260 stray cats were evaluated, using conventional polymerase chain reaction tests (cPCRs), for the presence of DNA associated with Rickettsia species, Anaplasma phagocytophilum and Ehrlichia species. Positive cPCR results occurred in 127/260 subjects (48.9%; 95% confidence interval [CI] = 40.7–58.1), with a prevalence of 31.9% (83/260, 95% CI = 25.4–39.6) for Rickettsia species, 17.7% (46/260, 95% CI= 13.0–23.6) for A phagocytophilum, and 5.4% (14/260, 95% CI = 2.9–9.0) for Ehrlichia species. There was no statistical association between a positive PCR test for vector-borne infections surveyed and colony location, age, gender, body condition score or complete blood count abnormalities, nor feline immunodeficiency virus, feline leukaemia virus or Toxoplasma gondii status. The only variable linked to positive PCR results was detection of signs of ocular infection and PCR positivity for Rickettsia species ( P = 0.04, odds ratio [OR] = 2.2, 95% CI = 1.1–4.4, P = 0.02). There is a significant prevalence of vector-borne infections with zoonotic potential in urban stray cats in Milan. Thus, dogs and pet cats with outdoor access should be monitored and treated for ectoparasites on a regular basis to minimise risks of disease and the potential transmission of zoonotic agents to people.